(untitled) (Nordic Journal of Practical Theology, 2019)
Case studies in the field of spiritual care provide us with important information in the search for good care practices. However, the research process in the Dutch mental health care research community shows that good reflection on practice is not self-evident. To investigate this gap between practice and reflection we introduce the concept of professional body of knowledge (PBOK) in this field. On the one hand, practitioners need to adopt an attitude of not-fully-knowing in order to be open to fruitful atonement in communication. On the other hand, they need methodological reflection to make the skills involved explicit so that they can improve the interactions next time. With the help of one singular case study about moral counselling in the context of a suicide agreement between two adolescents, we show the case study approach in the Netherlands as well as a first application of our working model on PBOK.